2004
DOI: 10.1016/j.virusres.2004.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of synonymous codon usage in SARS Coronavirus and other viruses in the Nidovirales

Abstract: In this study, we calculated the codon usage bias in severe acute respiratory syndrome Coronavirus (SARSCoV) and performed a comparative analysis of synonymous codon usage patterns in SARSCoV and 10 other evolutionary related viruses in the Nidovirales. Although there is a significant variation in codon usage bias among different SARSCoV genes, codon usage bias in SARSCoV is a little slight, which is mainly determined by the base compositions on the third codon position. By comparing synonymous codon usage pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
160
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(187 citation statements)
references
References 41 publications
26
160
1
Order By: Relevance
“…So the content of A or T ending codons is a important factor. The ENC value and GC 3S content, two important codon usage indices, have been widely used to explore the codon usage variation among different genes [42][43][44]. Values of ENC range From 20(when only one codon is used per amino acid) to 61(when all synonyms are used with equal frequency).…”
Section: Discussionmentioning
confidence: 99%
“…So the content of A or T ending codons is a important factor. The ENC value and GC 3S content, two important codon usage indices, have been widely used to explore the codon usage variation among different genes [42][43][44]. Values of ENC range From 20(when only one codon is used per amino acid) to 61(when all synonyms are used with equal frequency).…”
Section: Discussionmentioning
confidence: 99%
“…Each gene is presented as a 59-dimensional vector, and each dimension corresponds to the RSCU value of one sense codon, excluding AUG, UGG, and three stop codons (Gu et al, 2004). For a contingency table with I rows and J columns, the plot produced by correspondence analysis contains two sets of points: one set of I points that corresponds to the rows, and one set of J points that corresponds to the columns.…”
Section: Correspondence Analysismentioning
confidence: 99%
“…Genes or species that are strongly associated, as measured by their chi-square distances, lie in a similar direction from the origin (Johnson and Wichern, 2002;Perrière and Thioulouse, 2002). The chi-square distance between two coordinates with the same row or column value, called the Euclidean distance (Perrière and Thioulouse, 2002;Gu et al, 2004), has important statistical meaning, whereas there is no significant statistical meaning attached to the relationship between the row coordinate and column coordinate. The SigmaPlot 8.0 program was used to create graphical correspondence analysis plots using coordinates that consisted of the first- and second-dimensional factors that resulted from the correspondence analysis.…”
Section: Correspondence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis found that synonymous codon usage pattern changed at distinct sites along a coding sequence (14), balances of strong versus weak base pair bonding (15,16), maintenance of DNA and RNA secondary structure (17), and translational efficiency and fidelity (6). Aujeszky's disease, which is provoked by the pathogenic factor of Pseudorabies virus (PRV) (also known as Suid herpesvirus 1,, is a regularly lethal disease with a global distribution that influences swine, mainly and other domestic and wild animals incidentally (18)(19)(20)(21)(22). PRV belongs to the genus Varicellovirus, subfamily alpha herpesvirinae, which is a swine alpha herpesvirus (20,(23)(24)(25)(26) …”
Section: Introductionmentioning
confidence: 99%